Decision Making In Public Junior High Schools Of Tangerang City And Regency - Suhardi, Muhamad; Huda, Syafaat Ariful (International Journal for Educational and Vocational Studies, 2020)
The purpose of this research is  to  determine the influence of managerial ability on headmasters decision making in Junior High School of Counties and Tangerang City. The research used survey method with path analysis applied in testing hypothesis. Technique of data collecting is using instrument in the form of questionnaire. The number of 60 headmasters as sample by simple was selected random sampling.The result of this research indicated that : there is a direct positive effect of managerial ability to headmasters decision making.